Perlindungan Konsumen Terhadap Produk Makanan Kadaluarsa di Kota Batam - Rina Shahriyani Shahrullah; Hindra Hindra (Journal of Law and Policy Transformation, 2020)
The purpose of this study is analyzing the setting of Law No. 8 of 1999 on Consumer Protection Against Expired Food Products in Kota Batam.Menganalisis application of the impact of Law No. 8 of 1999 on Consumer Protection Against Expired Food Products in Kota Batam.Menganalisis and find solutions Law No. 8 of 1999 against the negative effects of using products Food Expiration in Batam. This research is classified as qualitative research, and the kind of empirical legal research / sociological, and the object of research is the primary data Interview and observation data coupled with secondary data literature study.The results of this thesis study can be concluded as follows: Implementation of Law No. 8 of 1999 on Consumer Protection against food products expired in Batam practically found that business (shop owners) already have a sense of absolute responsibility (strick lialibility), where when consumers konplein in case the goods expired they had provide compensation in accordance with the agreement. Against the expired goods store owners take action to restore the goods to the seller, gutted and there was also selling goods at bargain prices